Differential Diagnosis between Child Abuse and Infantile Cortical Hyperostosis: A Case Report and Literature Review - Du-Yeon Lee (MDPI AG, 2021)
Child abuse is a major public health problem that can lead to critical consequences for the child and family. However, early identification of abuse may be difficult. An 8-month-old boy presented with extensive periosteal reaction in both upper and lower long bones. There was no specific history of injury. Caffey disease was initially considered as the diagnosis because the patient displayed fever and hyperostosis of multiple bones with elevated erythrocyte sedimentation rates and C-reactive protein and alkaline phosphatase levels. However, we suspected child abuse based on the clinical and radiological features. We eventually found out that the child had been injured through child abuse and were able to treat him. We report this case because child abuse cases may be confused with Caffey disease. This case report can, therefore, help distinguish between Caffey disease and child abuse.